Exome sequencing provides additional evidence for the involvement of ARHGAP29 in Mendelian orofacial clefting and extends the phenotypic spectrum to isolated cleft palate. Issue 1 (20th January 2017) - Liu, Huan; Busch, Tamara; Eliason, Steven; Anand, Deepti; Bullard, Steven; Gowans, Lord J.J; Nidey, Nichole; Petrin, Aline; Augustine‐Akpan, Eno‐Abasi; Saadi, Irfan; Dunnwald, Martine; Lachke, Salil A.; et al.
Abstract : Background: Recent advances in genomics methodologies, in particular the availability of next‐generation sequencing approaches have made it possible to identify risk loci throughout the genome, in particular the exome. In the current study, we present findings from an exome study conducted in five affected individuals of a multiplex family with cleft palate only. Methods: The GEnome MINIng (GEMINI) pipeline was used to functionally annotate the single nucleotide polymorphisms, insertions and deletions. Filtering methods were applied to identify variants that are clinically relevant and present in affected individuals at minor allele frequencies (≤1%) in the 1000 Genomes Project single nucleotide polymorphism database, Exome Aggregation Consortium, and Exome Variant Server databases. The bioinformatics tool Systems Tool for Craniofacial Expression‐Based Gene Discovery was used to prioritize cleft candidates in our list of variants, and Sanger sequencing was used to validate the presence of identified variants in affected and unaffected relatives. Results: Our analyses approach narrowed the candidates down to the novel missense variant in ARHGAP29 (GenBank: NM_004815.3, NP_004806.3;c.1654T>C [p.Ser552Pro]. A functional assay in zebrafish embryos showed that the encoded protein lacks the activity possessed by its wild‐type counterpart, and migration assays revealed that keratinocytes transfected with wild‐type ARHGAP29 migrated faster than counterparts transfected with the p.Ser552Pro ARHGAP29 variant or empty vector (control). Conclusion: These findings reveal ARHGAP29 to be a regulatory protein essential for proper development of the face, identifies an amino acid that is key for this, and provides a potential new diagnostic tool.Birth Defects Research 109:27–37, 2017. © 2016 Wiley Periodicals, Inc.